2019
DOI: 10.1159/000500525
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Circulating Chromogranin A as a Biomarker of Bronchopulmonary Neuroendocrine Neoplasia: A Systematic Review and Meta-Analysis

Abstract: Background: Management of bronchopulmonary neuroendocrine neoplasia (NEN; pulmonary carcinoids [PCs], small-cell lung cancer [SCLC], and large cell neuroendocrine carcinoma) is hampered by the paucity of biomarkers. Chromogranin A (CgA), the default neuroendocrine tumor biomarker, has undergone wide assessment in gastroenteropancreatic neuroendocrine tumors. Objectives: To evaluate CgA in lung NEN, define its clinical utility as a biomarker, assess its diagnostic, prognostic, and predictive efficacy, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 107 publications
3
20
0
1
Order By: Relevance
“…Of the 43 BPNEN patients, all were NETest-positive; however, only 11 (26%) were CgA-positive. Our results confirm previous observations that CgA measurements are ineffective in lung NENs [5, 17] and that the NETest is significantly more effective than CgA positivity as a diagnostic for lung NENs [37].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Of the 43 BPNEN patients, all were NETest-positive; however, only 11 (26%) were CgA-positive. Our results confirm previous observations that CgA measurements are ineffective in lung NENs [5, 17] and that the NETest is significantly more effective than CgA positivity as a diagnostic for lung NENs [37].…”
Section: Discussionsupporting
confidence: 91%
“…Finally, although CgA is considered ineffective as a biomarker in BPNENs [5] and recent studies and meta-analyses [17] have confirmed its lack of utility, we had the opportunity to evaluate whether it was as effective as the NETest. Of the 43 BPNEN patients, all were NETest-positive; however, only 11 (26%) were CgA-positive.…”
Section: Discussionmentioning
confidence: 99%
“…The positive NETest findings in IPMN and colon adenocarcinoma are consistent with observations from an earlier publication that identified minor overlap [35]. Similarly, positive NETest scores in lung neoplasia have recently been reported based upon the existence of neuroendocrine elements in lung cancer [36]. A histopathologically verified colon NEC and a G3 gastric NEC were both NETest-positive (score: 87 and 80, respectively) as would be predicted in tumors that have a neuroendocrine genotype and phenotype.…”
Section: Discussionsupporting
confidence: 87%
“…Some reports consider it to correlate with tumor biology and size and to provide information in respect of outcome [ 29 , 30 ]. More recently, the enthusiasm for the clinical use of CgA is much diminished as rigorous studies have demonstrated low utility [ 31 35 ]. Of particular concern has been the inability of the different assays to produce comparable data [ 36 – 41 ].…”
Section: Introductionmentioning
confidence: 99%